1998
DOI: 10.1021/jf9805606
|View full text |Cite
|
Sign up to set email alerts
|

Nonvolatile Taste Components of Ear Mushrooms

Abstract: Five kinds of ear mushrooms are commercially available in Taiwan, including black, red, jin, snow, and silver ears. Ash contents ranged from 2.05 to 6.14% of dry weight. Carbohydrate contents ranged from 68.88 to 88.14%. The jin and snow ears contained high amounts of crude fat (4.48 and 4.54%, respectively). The jin and snow ears also contained high amounts of crude fiber (11.69 and 8.51%, respectively). Crude protein contents were high in the black and snow ears (15.46 and 12.53%, respectively). Ear mushroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The absence of sulfur-containing amino acid could be due to their instability in the course of the experiment, although it is known that these are not very common amino acids in mushroom. Table 4 divides the free amino acids into several classes on the basis of their taste characteristics as described by Mau et al (1998aMau et al ( , 1998bMau et al ( , 1998c. Aspartic and glutamic acids are classified as monosodium glutamate-like (MSG-like) components that contribute to the most typical mushroom taste, MSG-like and sweetness components would mainly be responsible for the attractive taste of G. frondosa.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of sulfur-containing amino acid could be due to their instability in the course of the experiment, although it is known that these are not very common amino acids in mushroom. Table 4 divides the free amino acids into several classes on the basis of their taste characteristics as described by Mau et al (1998aMau et al ( , 1998bMau et al ( , 1998c. Aspartic and glutamic acids are classified as monosodium glutamate-like (MSG-like) components that contribute to the most typical mushroom taste, MSG-like and sweetness components would mainly be responsible for the attractive taste of G. frondosa.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other ear mushroom, TFS contained the lowest amount of crude fiber, and other ingredients were in the middle position. The contents of moisture and crude fiber were higher, and carbohydrate, ether extract (lipid), ash and protein in TFS were lower when compared with the silver ear (Tremella fuciformis) cultivated in Taiwan (China) [3]. Elemental composition of TFS was 1.71 % N, 40.35 % C, 6.25 % H and 0.20 % S. The content of total nitrogen was in high consistency with the content of total nitrogen measured by using the method of Kjeldahl [3].…”
Section: Proximate Analysis Of Tfsmentioning
confidence: 95%
“…Aspartic and glutamic acids were the highest amounts in TFS. The free amino acids contents of MSG-like components in silver ear (Taiwan) were 0.009 [3]. Glycine, alanine, threonine, glutamic acids and aspartic were the main taste-active components in mushrooms [3].…”
Section: Analysis Of Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In research of A. polytricha, the culture media (Kinjo & Kondo, 1979;Lin, 1991), the components (Yoshida et al, 1986(Yoshida et al, , 1996Lee et al, 1995;Cheung, 1997;Mau et al, 1998), antitumor activity (Misaki et al, 1979), antioxidative activity (Zhou & Yu, 2000) and effects of cholesterol (Arakawa et al, 1977;Tamaki et al, 1997) have been reported.…”
mentioning
confidence: 99%